Ac Susceptibility Measurements and Mechanical Performance of Bulk MgB2 - Öztürk, Özgür; Aşıkuzun, Elif; Kaya, Şeydanur; Erdem, Murat; Safran, Serap; Kılıç, Ahmet; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2015)
The effects of Ar ambient pressure (vacuum and 0, 10, and 20 B) and annealing times (0.5 and 1 h) on microstructural, superconducting, and mechanical properties of bulk superconducting MgB2 are investigated. The samples are produced using the solid-state reaction method. X-ray diffraction (XRD) and scanning electron microscopy (SEM) measurements are performed for determination of the crystal structure and surface morphology of MgB2 samples, respectively. The superconducting properties are studied by AC magnetic susceptibility measurements. Microhardness analyses are made using the Vickers microhardness test for determination of mechanical properties of all samples. Increasing the Ar pressure decreases the lattice parameters and hence the average grain size. Increasing the annealing time results in larger lattice parameters and larger grain formation. The susceptibility measurements revealed a two-step transition which is reminiscent of granular superconductors. The intra-grain transition temperature is determined to be 38.4 K for all samples. The inter-grain transition temperature of 37.2 K is obtained for samples produced under Ar ambient pressure. The samples produced under Ar ambient pressure have better superconducting properties than the ones produced in vacuum. Increasing the annealing time under vacuum further decreases the superconducting properties probably due to Mg loss.
Keywords: MgB2 superconductors; XRD; Susceptibility; SEM; Vickers Microhardness; 3. Good health